Tinjauan Risiko Keselamatan Kerja Jalur Produksi Melalui Job Safety Analysis pada Stasiun Rantaian PKS Sei Intan - Chindy Elsana Revadi; Yunitri Maylia Mahady; Alfin Fauzi Malik; Dini Wahyuni (Journal of Industrial Innovation and Safety Engineering (JINSENG), 2026)
Palm oil mill operations entail the use of various equipment and machinery, including hot wagons, capstans, hoisting cranes, slings, steam, slippery floors, noise, and work at height. The study's key findings are as follows: hazards have been identified, initial risks have been assessed, and priority controls have been proposed at the Chain Station. These findings are based on a Job Safety Analysis of the Sei Intan Palm Oil Factory. The methods used in this study combine direct observation, interviews, documentation, and risk assessment. Ten hazards were identified, categorised as three medium, four high and three extreme risks. The innovation lies in the translation of a general IBPR document into task-based JSA and shift safety patrol checklists.